Development of a Supervision Model to Enhance Instructional Management Competence for Pre-Service Teachers in the Faculty of Education, Phuket Rajabhat University - Sadjarak, Somkiat; Boriwatanan, Nipon; Phumpaka, Aujcharapun (Journal of Graduate Research, 2025)
The objectives of this research article were to: 1) develop a supervisory model to enhance instructional competence, 2) implement the supervisory model to enhance instructional competence, and 3) evaluate the satisfaction levels of pre-service teachers regarding the use of the model. The research was conducted among pre-service teachers enrolled in the Faculty of Education at Phuket Rajabhat University. The target group consisted of 55 pre-service teachers from various majors who undertook their teaching practicum during the second semester of the 2024 academic year, 20 school administrators, 22 mentor teachers (two per major), 22 university supervisors (two per major), 20 school board representatives, and five subject-matter experts. All participants were selected through purposive sampling. The research instruments consist of a document analysis form, an interview guide, a supervision handbook, an instructional competence assessment form, and a satisfaction evaluation form. The data were analyzed using the mean (𝑥̅) and standard deviation (S.D.). The findings revealed that: 1) The supervisory model for enhancing instructional competence, referred to as the “SKS Model,” consists of guiding principles, objectives, key components, implementation conditions, supporting factors, operational procedures, and expected outcomes. The instructional competence of pre-service teachers significantly improved after the implementation of the SKS Model. and 3) pre-service teachers expressed a high level of satisfaction with the “SKS Model” for enhancing instructional competence.